Smokestacks in the hills : rural-industrial workers in West Virginia - Martin, Lou (Working class in American history., 2015)
Long considered an urban phenomenon, industrialization also transformed the American countryside. Lou Martin weaves the narrative of how the relocation of steel and pottery factories to Hancock County, West Virginia, created a rural and small-town working class - and what that meant for communities and for labor. The result is an illuminating consideration of capital mobility, the ways in which changing work experiences defined gender roles, and the erroneous but persistent myth that modernizing forces bulldozed docile local cultures.